Nanocapsules Containing Neem (Azadirachta Indica) Oil: Development, Characterization, and Toxicity Evaluation - Pasquoto-Stigliani, Tatiane; Campos, Estefânia V. R. [UNESP]; Oliveira, Jhones L. [UNESP]; Silva, Camila M. G.; Bilesky-José, Natalia; Guilger, Mariana; Troost, Johann; Oliveira, Halley C.; Stolf-Moreira, Renata; Fraceto, Leonardo F. [UNESP]; De Lima, Renata (Springer Nature, 2017)
In this study, we prepared, characterized, and performed toxicity analyses of poly(ϵ-caprolactone) nanocapsules loaded with neem oil. Three formulations were prepared by the emulsion/solvent evaporation method. The nanocapsules showed a mean size distribution around 400 nm, with polydispersity below 0.2 and were stable for 120 days. Cytotoxicity and genotoxicity results showed an increase in toxicity of the oleic acid + neem formulations according to the amount of oleic acid used. The minimum inhibitory concentrations demonstrated that all the formulations containing neem oil were active. The nanocapsules containing neem oil did not affect the soil microbiota during 300 days of exposure compared to the control. Phytotoxicity studies indicated that NC-20 (200 mg of neem oil) did not affect the net photosynthesis and stomatal conductance of maize plants, whereas use of NC-10 (100:100 of neem:oleic acid) and NC-15 (150:50 of neem:oleic acid) led to negative effects on these physiological parameters. Hence, the use of oleic acid as a complement in the nanocapsules was not a good strategy, since the nanocapsules that only contained neem oil showed lower toxicity. These results demonstrate that evaluation of the toxicity of nanopesticides is essential for the development of environmentally friendly formulations intended for applications in agriculture.